2014
DOI: 10.1186/s13054-014-0567-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing external ventricular drain-related ventriculitis by means of local inflammatory response: soluble triggering receptor expressed on myeloid cells-1

Abstract: IntroductionExternal ventricular drainage (EVD)-related ventriculitis is one of the most severe complications associated with the use of EVDs. Establishing an early and certain diagnosis can be difficult in critically ill patients. We performed this prospective study to evaluate the usefulness of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) determination in cerebrospinal fluid (CSF) in the diagnosis of ventriculitis.MethodsA prospective observational study was conducted of 73 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
12
0
4
Order By: Relevance
“…This finding is in line with those of previous reports. 7,15 Two studies confirmed significantly increased TLC in patients with ventriculitis, but results regarding glucose, protein, and percentage of neutrophils in CSF or serum markers WBCC and CRP were not conclusive. 17,34 Another recently published study showed that the cell index (ratio of leukocytes to erythrocytes in CSF and leukocytes to erythrocytes in the peripheral blood) had a good diagnostic potential for predicting ventriculitis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with those of previous reports. 7,15 Two studies confirmed significantly increased TLC in patients with ventriculitis, but results regarding glucose, protein, and percentage of neutrophils in CSF or serum markers WBCC and CRP were not conclusive. 17,34 Another recently published study showed that the cell index (ratio of leukocytes to erythrocytes in CSF and leukocytes to erythrocytes in the peripheral blood) had a good diagnostic potential for predicting ventriculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Other substrates, such as CSF lactate, cytokine levels, and serum procalcitonin, are also disturbed after SAH. Although procalcitonin has been shown to be able to discriminate between a systemic inflammatory response syndrome and a systemic infection [34], the value to differentiate between aseptic and bacterial ventriculitis of this and other substrates is limited [3338]. Polymerase chain reaction of the CSF for the detection of bacterial pathogens has been shown to have a low sensitivity in patients with an external catheter-related bacterial ventriculitis and patients with aseptic ventriculitis after surgery, but assays are getting more sensitive [3942].…”
Section: Discussionmentioning
confidence: 99%
“…Debido a estos factores, el estudio de LCR sigue siendo la clave para el diagnóstico de ventriculitis. Sin embargo, la irritación meníngea debido a la presencia de productos de degradación en la sangre podría (10) afectar glucosa, proteínas y mediciones de recuento de leucocitos en el LCR . Por todo esto no se puede establecer un valor absoluto de parámetros citoquímicos para indicar o sospechar infección.…”
Section: Introductionunclassified
“…Los bacilos Gram negativos son una etiología creciente que complican las posibilidades terapéuticas dada su (1,(12)(13)(14)(15) estrecha relación con multirresistencia . Actualmente hay muchas publicaciones en donde los (1,5,10,12) gérmenes más frecuentes son los bacilos Gram negativos .…”
Section: Introductionunclassified
See 1 more Smart Citation